2016
DOI: 10.3389/fimmu.2016.00549
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Characterization of Human CD8 T Suppressor Cells

Abstract: Bidirectional interactions between dendritic cells and Ag-experienced T cells initiate either a tolerogenic or immunogenic pathway. The outcome of these interactions is of crucial importance in malignancy, transplantation, and autoimmune diseases. Blockade of costimulation results in the induction of T helper cell anergy and subsequent differentiation of antigen-specific CD8+ T suppressor/regulatory cells (Ts). Ts, primed in the presence of inhibitory signals, exert their inhibitory function in an antigen-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 105 publications
1
20
0
Order By: Relevance
“…We recently described a novel human regulatory CD8 + HLA-DR + T cell population present in adult and umbilical venous blood samples ( 5 ) representing a small subset in peripheral blood (PB) or cord blood mononuclear cells (CBMCs). The comparison between CD8 + HLA-DR − and CD8 + HLA-DR + T cells shows similar expression of the co-stimulatory molecule CD28, which differentiates them from the previously characterized CD8 + CD28 −/low T suppressor cells originally generated in vitro by multiple rounds of T cell stimulation by allogenic APCs ( 6 ). Another natural CD8 + Treg population distinguished by expression of CD122 ( 7 ) was described in mice, but has not yet been identified in humans, and appear to exert their suppressor effect via IL-10.…”
Section: Introductionmentioning
confidence: 55%
“…We recently described a novel human regulatory CD8 + HLA-DR + T cell population present in adult and umbilical venous blood samples ( 5 ) representing a small subset in peripheral blood (PB) or cord blood mononuclear cells (CBMCs). The comparison between CD8 + HLA-DR − and CD8 + HLA-DR + T cells shows similar expression of the co-stimulatory molecule CD28, which differentiates them from the previously characterized CD8 + CD28 −/low T suppressor cells originally generated in vitro by multiple rounds of T cell stimulation by allogenic APCs ( 6 ). Another natural CD8 + Treg population distinguished by expression of CD122 ( 7 ) was described in mice, but has not yet been identified in humans, and appear to exert their suppressor effect via IL-10.…”
Section: Introductionmentioning
confidence: 55%
“…CD8 + T cells were MACS-purified and then cocultivated with APAcCNF-DC for 6 days, followed by their flow cytometry analysis according to the markers proposed for suppressor CD8 + T cells. 45 It was found that, even in the absence of CD4 + T cells, APAcCNF-DC induced significantly higher percentage of IL-10 + cells within the CD8 + CD25 + population (Figure 6A and B), whereas CD8 + CD25 -T cells did not express significant levels of IL-10 (data not shown). The increased IL-10 expression was detected in both IFN-γ + and IFN-γ -CD8 + CD25 + T cells, but a higher percentage of CD8 + CD25 + IFN-γ + T cells expressed IL-10.…”
Section: Differentiated With Ncnf But Not Ccnf and Apaccnf Inducmentioning
confidence: 84%
“…This assumption was underpinned by Battaglia and co-authors [ 10 ] and Heeren and co-authors [ 11 ], who showed that CD8 + FoxP3 + Т cells were more frequent in metastatic tumor-draining lymph nodes in early-stage cervical cancer. Apart from oncological diseases, CD8 Tregs are thought to play an important role in establishment of chronic viral infection, including herpesviruses (EBV, CMV), HCV and HIV (discussed in [ 38 ]). It is also possible that HPV engages CD8 Tregs for maintaining its long-term persistence, which may underlie an increase in the frequency of CD8 Tregs observed at earliest stages of CC progression.…”
Section: Discussionmentioning
confidence: 99%